(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Public libraries have evolved beyond repositories of books into dynamic catalysts for social change, fostering inclusion, empowerment, and community resilience. This article examines how libraries act as agents of change through diverse roles—from education and social services to cultural preservation. Through an analysis of scholarly literature and five illustrative case studies from India, Africa, Latin America, and Finland, this study highlights their evolving impact on marginalized communities, crisis response, and social equity. The article concludes with actionable suggestions to amplify these roles and a reflection on the future of libraries as transformative public institutions.